2016
DOI: 10.1016/j.jpedsurg.2016.02.085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body mass index percentile on pediatric gastrointestinal surgery outcomes

Abstract: Background/Purpose Pediatric obesity is an important public health concern, yet its effect on surgical outcomes is poorly understood. The purpose of this study was to determine if age and gender-specific body mass index (BMI) percentile influences complications and hospital resource utilization following pediatric gastrointestinal surgeries. Methods Patients aged age ≥2 to <18 years who underwent appendectomy or other gastrointestinal operations were identified in the 2012 - 2013 Pediatric National Surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 26 publications
4
24
2
Order By: Relevance
“… 4 A study of a large national pediatric database that compared patients who underwent appendectomy to patients undergoing other intestinal operations showed that obese appendectomy pediatric patients had significantly longer hospital LOS compared nonobese patients, but no significant difference in LOS was seen between obese and nonobese patients undergoing other intestinal operations. 5 Other studies have reported worse outcomes in obese adults and longer operating times in obese adults and children. 6 - 8 The purpose of this study was to investigate the effect of obesity in adult and pediatric patients undergoing appendectomy at our institution.…”
Section: Introductionmentioning
confidence: 97%
“… 4 A study of a large national pediatric database that compared patients who underwent appendectomy to patients undergoing other intestinal operations showed that obese appendectomy pediatric patients had significantly longer hospital LOS compared nonobese patients, but no significant difference in LOS was seen between obese and nonobese patients undergoing other intestinal operations. 5 Other studies have reported worse outcomes in obese adults and longer operating times in obese adults and children. 6 - 8 The purpose of this study was to investigate the effect of obesity in adult and pediatric patients undergoing appendectomy at our institution.…”
Section: Introductionmentioning
confidence: 97%
“…Only a few studies in children undergoing non-cardiac surgery have sought an association between anthropometric classification and postoperative morbidity. Previous studies using the aggregate NSQIP paediatric dataset have shown that children in the ≤5th weight percentile experienced higher rates of postoperative transfusion and reintubation, 20 while children undergoing appendectomy 21 and urological procedures 22 who met BMI percentile definitions of overweight/obese were more likely to experience postoperative wound complications. However, a limitation of existing anthropometric classification schemes is that they were developed to define the nutritional state of an individual relative to a reference population of ‘healthy’ children.…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with this, we observed a trend toward a longer duration of GI symptoms prior to admission in Black compared to Hispanic/Latino children (data not shown), which was one of the clinical features associated with LOS. Obesity has previously been associated with delay in diagnosis and increased risk of post-operative complications, including wound infection and dehiscence ( 20 – 22 ). In our study children with BMIs greater than the 85 th percentile had higher oxygen requirements and more episodes of sepsis; however, this did not result in overall longer LOS.…”
Section: Discussionmentioning
confidence: 99%